2014
DOI: 10.1519/jsc.0000000000000651
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Characteristics and Body Composition of NCAA Division I Football Players

Abstract: The purpose of this study was to examine muscle characteristics of the vastus lateralis (VL) and body composition of National Collegiate Athletic Association (NCAA) Division I football players. Sixty-nine Division I football players (mean ± SD; age: 20.0 ± 1.1 years; height: 186.2 ± 7.0 cm; body mass: 106.3 ± 21.1 kg; %fat: 17.8 ± 4.6%) were stratified by player position, race, year, and starter status. A panoramic scan of the VL was performed using a GE Logiq-e B-mode ultrasound. Muscle cross-sectional area (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 50 publications
10
58
1
1
Order By: Relevance
“…When using this technique to evaluate division I football players, Melvin et al (15) found that while offensive (OL) and defensive linemen (DL) had significantly greater %fat than other positions, they had EI values similar to that of other positions, demonstrating similar muscle quality. Compared to values reported by Melvin et al (2014), throwers in the current study had similar EI values as football players (range = 54.5 – 65.8 a.u.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When using this technique to evaluate division I football players, Melvin et al (15) found that while offensive (OL) and defensive linemen (DL) had significantly greater %fat than other positions, they had EI values similar to that of other positions, demonstrating similar muscle quality. Compared to values reported by Melvin et al (2014), throwers in the current study had similar EI values as football players (range = 54.5 – 65.8 a.u.).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that body composition varies by sport (4, 24), as well as by position, and event within a sport (13, 15, 22). Evaluation of body composition has been previously shown to be an important determinant of health and performance (12), however, little data quantifying body composition characteristics of track and field athletes exists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of muscle tightness vis-à-vis extensibility or flexibility has been documented among young sports participants, which tends to correlate with the chosen type of athletic competition (15,16). Different degrees of constitutional muscular tonicity (or tightness) may be advantageous in one or another sport (17), as is observed for strength and physical endurance (18).…”
Section: Introductionmentioning
confidence: 99%
“…Among offensive linemen on Division I collegiate teams, body weights in excess of 300 lb (136 kg) and BMI values in excess of 35 kg/m 2 are typical [15][16][17][18] and are accompanied by objective risk factors for the development of metabolic syndrome and cardiovascular disease. [19][20][21][22] The body size and risk factor trends among National Football League players-most of whom came from Division I collegiate programs-are even greater.…”
mentioning
confidence: 99%